Transforming music education - Jorgensen, Estelle Ruth (Counterpoints (Bloomington, Ind.), 2003)
"Brilliant ... important reading for those who teach music, who write the curricular plans for teaching it, and who guide prospective teachers to the profession ... It is a must-read, for it awakens thoughts about why we teach and how."--Patricia Shehan CampbellThis quintet of essays examines the reasons why music education should be transformed, investigates the nature of education and musical transformation, and suggests alternative educational models and strategies. Estelle Jorgensen frames her argume